The relationships between perceived individual and team characteristics, individual and team learning activities with effectiveness in nursing teams - Anselmann, Veronika; Brouwer, Jasperina; Mulder, Regina H. (Frontiers in Psychology, 2023)
Introduction: Team learning is crucial due to the shortage of nurses and the contemporary increase in the deployment of nurses in times of crisis. This study investigates the extent to which individual learning activities (1) contribute to knowledge sharing in teams and (2) impact the effectiveness of nursing teams. Furthermore, we want to obtain more insight into whether (3) the antecedents of individual psychological empowerment, teamwork preference, and team boundedness contribute to individual learning activities and knowledge sharing in nursing teams. Method: We conducted a cross-sectional questionnaire study of 149 gerontological nurses working in 30 teams in Germany. They completed a survey measuring knowledge sharing, teamwork preference, team boundedness, individual learning activities, psychological empowerment, and team effectiveness (as an indicator for performance). Results: The results of structural equation modeling indicate that individual learning activities contribute to knowledge sharing in teams and, hence, to a team’s effectiveness. In particular, psychological empowerment relates to individual learning activities. Teamwork preference and team boundedness relate to knowledge sharing. Discussion: The results indicate that accomplishment of individual learning activities plays an important role in nursing teams, because it links to knowledge sharing and, hence, to team effectiveness.